2009
DOI: 10.5539/ijbm.v4n3p43
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Interest Rate and Stock Price: Empirical Evidence from Developed and Developing Countries

Abstract: Stock exchange and interest rate are two crucial factors of economic growth of a country. The impacts of interest rate on stock exchange provide important implications for monitory policy, risk management practices, financial securities valuation and government policy towards financial markets. This study seeks evidence supporting the existence of share market efficiency based on the monthly data from January 1988 to March 2003 and also shows empirical relationship between stock index and interest rate for fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 32 publications
8
68
1
4
Order By: Relevance
“…Uddin and Alam [46] found that Interest Rate has a significant negative relationship with Share Price and Changes of Interest Rate has a significant negative relationship with Changes of Share Price. Similar results were found by Alam and Uddin [47]. Osahon and Oriakhi [20] found that interest rates are negatively related to stock prices.…”
Section: Literature Reviewsupporting
confidence: 78%
See 1 more Smart Citation
“…Uddin and Alam [46] found that Interest Rate has a significant negative relationship with Share Price and Changes of Interest Rate has a significant negative relationship with Changes of Share Price. Similar results were found by Alam and Uddin [47]. Osahon and Oriakhi [20] found that interest rates are negatively related to stock prices.…”
Section: Literature Reviewsupporting
confidence: 78%
“…Some researchers found a negative relationship between interest rate and stock prices [44,46,47] and this generally assumed negative relationship is partly based on the view that a decrease in interest rates leads to lower borrowing costs for firms, higher future profits, and thus higher stock prices. It is also argued that lower interest rates prompt investors to move money from the bond market to the equity market.…”
Section: Model Specification and Datamentioning
confidence: 99%
“…Conversely, if government interest rates fall, the move pushes the prices of all other investments upward‖. This is consistent with the research result posted by Alam (2009) that there is an inverse relationship between stock prices and interest rates. The valuation of financial assets must consequently re-establish a new equilibrium value as interest rate move that would make it competitive in terms of comparable yield available in the risk free market.…”
Section: Stock Marketsupporting
confidence: 80%
“…The study also discovers a unidirectional causality from interest rate change to stock market return. Alam and Uddin (2009) examined the impacts of interest rates on stock exchange for fifteen developed and developing countries including Bangladesh. They used the monthly Stock Exchange Index and interest rate data from January 1998 to March 2003 of fifteen countries and run the panel regression.…”
Section: Literature Reviewmentioning
confidence: 99%